Effect Of Addition Of L-Ascorbic Acid To Wheat Bread Dough On Blood Glucose Response, Glycemic Index And Glycemic Load In Normal Subject (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study was to determine the effect of ascorbic acid (Vitamin C) as improver in bread on blood glucose response (BGR), Glycemic Index (GI) and Glycemic Load (GL) in healthy subjects. Three concentration of ascorbic acid namely, 5ppm, 10ppm and 15 ppm concentration were added to Ab-Graib wheat flour of 72 and 90% extraction in making local flat bread. Chemical composition of flour and produced bread and sensory properties were determined in order to assess the quantity of bread intake by Volunteers (Undergraduate and Graduate students in collage of Agriculture and forestry, University of Mosul) with BMI between 20-24 Kg/m2. Results show that bread samples which fortified by ascorbic acid had good and acceptable sensory properties. Both GI and GL were reduced in both 72 and 90% wheat flour extraction rate. The effect of addition of ascorbic acid in decreasing GI and GL was more in bread made from 90% flour extraction than bread made from 72% flour extraction, and this may be because of the more dietary fibers that 90% flour extraction contained. It was concluded that addition of ascorbic acid in précised quantity resulted in decreasing GI of bread made of 72 and 90% flour extractions with minimal increasing in higher concentrations.